Islamic stock market relationship between developed and developing countries / Nor Afiqah Isdoros - Isdoros, Nor Afiqah (Faculty of Business and Management, 2015)
This study aims to assess empirically the relationship of Islamic stock market which is Dow Jones United States Islamic Market Index, Dow Jones Islamic Market Japan Index, Jakarta Stock Exchange Jakarta Islamic Index, Dow Jones Islamic Market Turkey Index to the Dow Jones Islamic Market World Malaysia Index. The countries are categorized into developed and developing countries. The periods of analysis for this research are from 24 April 2008 until 23 April 2015 by using daily closing price of stock indices in USD currency. The relevant data regarding these stock markets have been taken from Dow Jones Islamic Index series. The study used Unit Root Test, Normality Test, Simple Linear Regression and Multiple Linear Regression in order to investigate the relationship among those markets. From the result, it reveals that all these stock indices have a significant positive relationship towards Dow Jones Islamic Market World Malaysia Index.